Identification, Characterization, and Evaluation of Polymorphic Microsatellite Markers for Parentage Assignment in Pinctada fucata. Issue 1 (7th May 2018) - Zhu, Kecheng; Yu, Wenbo; Zhang, Dianchang; Guo, Huayang; Zhang, Nan; Jiang, Shigui
Abstract: Parentage analysis is a useful tool for establishing pedigree relationships in selective breeding. In this study, 31 microsatellite markers were tested, and 13 loci were subsequently used to identify parenthood in Pinctada fucata . According to simulation analysis, the power of nine loci to exclude false parents was 99.94%, and that of 10 loci was 99.95%. Moreover, using 10 loci and known parental and filial information, the cumulative assignment success rate to one true parental pair was as high as 99%. Of the 120 progeny tested, 93.3% were exclusively assigned to their parental pairs in mixed pedigrees. These results suggested that these microsatellite markers can be used for rapid and effective parentage assignment and contribute to the selective breeding of P. fucata .